2017
DOI: 10.3791/55079
|View full text |Cite
|
Sign up to set email alerts
|

Green and Low-cost Production of Thermally Stable and Carboxylated Cellulose Nanocrystals and Nanofibrils Using Highly Recyclable Dicarboxylic Acids

Abstract: Here we demonstrate potentially low cost and green productions of high thermally stable and carboxylated cellulose nanocrystals (CNCs) and nanofibrils (CNF) from bleached eucalyptus pulp (BEP) and unbleached mixed hardwood kraft pulp (UMHP) fibers using highly recyclable dicarboxylic solid acids. Typical operating conditions were acid concentrations of 50 - 70 wt% at 100 °C for 60 min and 120 °C (no boiling at atmospheric pressure) for 120 min, for BEP and UMHP, respectively. The resultant CNCs have a higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Bian and coworkers also reported a maleic acid catalyzed-hydrolysis reaction for the preparation of CNCs and CNFs. The bleached eucalyptus pulp and unbleached mixed hardwood kraft pulp were used as the raw materials, and typical operating conditions were acid concentrations of 50-70 wt.% at 100-120 ∘ C for 1-2 h. The results showed that CNCs with the length of approximately 239-336 nm were obtained, and CNFs could be gained by the further mechanical fibrillation of fibrous cellulosic solid residue [99]. Yu et al reported an approach for extracting carboxylated CNCs by citric acid/hydrochloric hydrolysis of MCC [100].…”
Section: Organic Acid Hydrolysismentioning
confidence: 99%
“…Bian and coworkers also reported a maleic acid catalyzed-hydrolysis reaction for the preparation of CNCs and CNFs. The bleached eucalyptus pulp and unbleached mixed hardwood kraft pulp were used as the raw materials, and typical operating conditions were acid concentrations of 50-70 wt.% at 100-120 ∘ C for 1-2 h. The results showed that CNCs with the length of approximately 239-336 nm were obtained, and CNFs could be gained by the further mechanical fibrillation of fibrous cellulosic solid residue [99]. Yu et al reported an approach for extracting carboxylated CNCs by citric acid/hydrochloric hydrolysis of MCC [100].…”
Section: Organic Acid Hydrolysismentioning
confidence: 99%
“…FTIR spectra were recorded by a Fourier transform infrared (FTIR) spectroscopy system (Spectrum Two, PerkinElmer, Waltham, MA) with a universal attenuated-total-reflection (ATR) probe. The carboxyl group contents of CNC samples were determined by conductometric titration as described previously. , UV–vis light transmittance spectra of DM-OA-CNC suspension (0.1 wt %) was measured in a wavelength range of 190–1100 nm using a spectrophotometer (Model 8453, Agilent Technologies, Inc., U.S.A.). X-ray diffraction patterns of the samples were recorded on a X-ray diffractometer (Bruker D8 Discover, Bruker Co., Billerica, MA).…”
Section: Characterizationsmentioning
confidence: 99%
“…Additionally, with the emergence of wearable electronic products in recent years, electronic packaging materials are required to be capable of bending and folding [27]. Cellulose nanofiber (CNF) has high yield, eco-friendly, and natural degradation properties [28], and CNF nano-paper has excellent strength and resistivity, and exhibits low thermal expansion coefficient, which is an ideal base for the preparation of a new flexible electronic substrate [29,30].…”
Section: Introductionmentioning
confidence: 99%